2012
DOI: 10.1063/1.4742815
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical reaction pathways in Eley-Rideal recombination of nitrogen from W(100)

Abstract: The scattering of atomic nitrogen over a N-pre-adsorbed W(100) surface is theoretically described in the case of normal incidence off a single adsorbate. Dynamical reaction mechanisms, in particular Eley-Rideal (ER) abstraction, are scrutinized in the 0.1-3.0 eV collision energy range and the influence of temperature on reactivity is considered between 300  and 1500 K. Dynamics simulations suggest that, though non-activated reaction pathways exist, the abstraction process exhibits a significant collision energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 104 publications
3
68
0
Order By: Relevance
“…In the present 6D calculations, the collinear case, as for most of H+H/metal systems with high binding energies, 13,14,23 contributes to less than 5% of the recombination cross section and rotational excitation is as high as vibrational one. As in other systems, 83,84 ER recombination is found to mainly occur via collision with surface atoms prior to recombination underlying the fact that the representation of the PES has to be accurate more specifically in ER entrance channels corresponding to large impact parameters where both PES are in really good agreement to DFT energies (see Fig. 3 at b = 1.585 Å).…”
Section: B Results and Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In the present 6D calculations, the collinear case, as for most of H+H/metal systems with high binding energies, 13,14,23 contributes to less than 5% of the recombination cross section and rotational excitation is as high as vibrational one. As in other systems, 83,84 ER recombination is found to mainly occur via collision with surface atoms prior to recombination underlying the fact that the representation of the PES has to be accurate more specifically in ER entrance channels corresponding to large impact parameters where both PES are in really good agreement to DFT energies (see Fig. 3 at b = 1.585 Å).…”
Section: B Results and Discussionmentioning
confidence: 50%
“…ER recombination is considered to take place whenever both hydrogen atoms reach the initial altitude of the projectile with a positive H 2 center-of-mass momentum along Z, an inter-atomic distance r ≤ 2.2 Å after only one rebound of the diatom center-of-mass along the trajectory. 83,84 In order to compare our results with experimental data, 10 we have also performed QCT calculations using a generalized Langevin oscillator (GLO) model [85][86][87][88][89] to account for surface temperature effects and energy exchange with phonons. 83,84 However, we have found that adding such ingredients in the dynamics simulations barely alter the results obtained within the rigid surface approximation (at least, as far as the total ER reaction cross sections and products energy distributions are concerned).…”
Section: A Methodology and Computational Detailsmentioning
confidence: 99%
“…Such a structure is much smaller and less extended on W(110) and consequently affects much less ER reactivity as a function of the incidence energy. [32][33][34] H 2 ER abstraction on tungsten also reveals distinct recombination mechanisms depending on the surface structure. On W(110), recombination occurs after rebound of the projectile on the W surface atoms in the close vicinity of the target.…”
mentioning
confidence: 99%
“…The former mechanism involves direct collision between a scattering atom (projectile) and an adsorbed species (target), 30 while the latter is governed by hyperthermal diffusion of the projectile onto the surface prior to abstraction. 31 The influence of the crystal face has been recently scrutinized theoretically for the Eley-Rideal (ER) recombination a) pascal.larregaray@u-bordeaux.fr of hydrogen and nitrogen on the W(100) and W(110) surfaces, [32][33][34][35][36] accounting for dissipation to surface phonons and electrons. 37 In these direct ultrafast processes, the surface is thought to mostly behave as a spectator.…”
mentioning
confidence: 99%
“…In contrast, ER reactions involve an incident projectile directly abstracting an adsorbate from the surface. The reaction proceeds promptly-as in a single collisionirrespective of surface temperature [2][3][4][5][6]. The projectile kinetic energy and potential energy gained by entering a deep chemisorption well allows reaction at low temperatures.…”
mentioning
confidence: 99%